Comparison of cefamandole, cephalothin, ampicillin, and chloramphenicol in experimental Escherichia coli meningitis. - Beam, T R (1980)
The activities of cefamandole, cephalothin, ampicillin, and chloramphenicol were compared in fulminant and temperate Escherichia coli meningitis in rabbits. Intensive dosing schedules were employed to achieve maximal therapeutic benefits with short-term treatment. In an 8-h schedule chloramphenicol was significantly more effective in sterilizing the cerebrospinal fluid and curing both fulminant and temperate infections than cefamandole or ampicillin. Cephalothin was without effect in fulminant meningitis. Cefamandole and ampicillin were equivalent in activity in this and longer (12- and 24-hr) treatment schedules. The therapeutic benefits of chloramphenicol were purchased via use of doses above those generally regarded as safe for human use. The mean serum, cerebrospinal fluid, and brain concentrations of chloramphenicol, cefamandole, and ampicillin were significantly greater in rabbits with fulminant meningitis than in those with temperate meningitis. The difference was of such magnitude as to support the need to monitor drug concentrations.